2009
DOI: 10.2353/ajpath.2009.081107
|View full text |Cite
|
Sign up to set email alerts
|

Increased Endogenous Estrogen Synthesis Leads to the Sequential Induction of Prostatic Inflammation (Prostatitis) and Prostatic Pre-Malignancy

Abstract: Prostatitis causes substantial morbidity to men, through associated urinary symptoms, sexual dysfunction, and pelvic pain; however, 90% to 95% of cases have an unknown etiology. Inflammation is associated with the development of carcinoma, and, therefore, it is imperative to identify and study the causes of prostatitis to improve our understanding of this disease and its role in prostate cancer. As estrogens cause prostatic inflammation, here we characterize the murine prostatic phenotype induced by elevated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 56 publications
(66 reference statements)
8
74
0
Order By: Relevance
“…Moreover, although androgens and estrogens both play significant roles in the prostate, their specific balance seems to be even more critical in maintaining prostate health and tissue homeostasis in adulthood. Collectively, animal data have revealed that elevated T in the absence of estrogens may lead to the development of hypertrophy and hyperplasia of the prostate gland but not to malignancy (34). In contrast, high estrogen levels and low T have been shown to lead to the development of inflammation with aging and in premalignant lesions (34).…”
Section: A B C Dmentioning
confidence: 99%
“…Moreover, although androgens and estrogens both play significant roles in the prostate, their specific balance seems to be even more critical in maintaining prostate health and tissue homeostasis in adulthood. Collectively, animal data have revealed that elevated T in the absence of estrogens may lead to the development of hypertrophy and hyperplasia of the prostate gland but not to malignancy (34). In contrast, high estrogen levels and low T have been shown to lead to the development of inflammation with aging and in premalignant lesions (34).…”
Section: A B C Dmentioning
confidence: 99%
“…For instance, it has been observed that 72% of Lewis rat developed spontaneous prostatitis with advancing age compared to only 27% for Wistar rats while the administration of 17β-estradiol or castration promoted the incidence and severity of non-bacterial prostatitis to 100% in old adult Wistar rats [20] . The up-regulation of the systemic endogenous estrogens, including serum 17β-estradiol, concomitant with a decrease in the serum testosterone level by overexpressing aromatase (AROM) in FVB/N mice has also been observed to induce a chronic inflammation at 48 wk of age [28] . The inflammatory responses in AROM +/+ mice was also associated with an enhanced number of mast cells, macrophages, neutrophiles and T-lymphocytes and culminated to the formation of prostatic intraepithelial neoplasias (PINs) at 52 wk of age [28] .…”
Section: Inflammation and Pcmentioning
confidence: 99%
“…The up-regulation of the systemic endogenous estrogens, including serum 17β-estradiol, concomitant with a decrease in the serum testosterone level by overexpressing aromatase (AROM) in FVB/N mice has also been observed to induce a chronic inflammation at 48 wk of age [28] . The inflammatory responses in AROM +/+ mice was also associated with an enhanced number of mast cells, macrophages, neutrophiles and T-lymphocytes and culminated to the formation of prostatic intraepithelial neoplasias (PINs) at 52 wk of age [28] . In this regard, a treatment of immortalized, nontransformed and androgen-responsive rat NRP-152 prostatic epithelial cell line with 17β-estradiol at concentrations 1-3 μmol/L for a period of 2-6 wk has also been observed to induce their capacity of forming colonies in soft agar and tumors in immunodeficient nude mice [29] .…”
Section: Inflammation and Pcmentioning
confidence: 99%
“…Among the factors predisposing to PC development, there are intense oxidative stress, inflammatory atrophies and fibrosis associated with severe tissue injuries, hormonal deregulation, and, more particularly, advancing age (1,10,13,44,(79)(80)(81)(82)(83). Although the cellular origin for different PC subtypes remains not precisely established, a growing body of evidence suggests that the accumulation of distinct genetic and/or epigenetic alterations in prostatic stem/progenitor cells, and more particularly during chronological aging and intense tissue injuries, may result in their malignant transformation into highly tumorigenic PC stem/progenitor cells (5,13, (70).…”
Section: Cellular Origin and Heterogeneity Of Pcmentioning
confidence: 99%